Development of Learning Media for the Course of Two-Stroke Gasoline Motors to Improve Students’ Learning Outcomes - Suyitno Suyitno; Iis Widianto; Suryaneta binti Masrul (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
Learning media of cylinder head cutting for 2-stroke gasoline motors are still limited. The students usually receive the materials only from lectures while the practices used uncut motorcycle props. Subsequently, the students hardly understand the form and the functions of the components. This study aimed at (1) developing the instructional media of two-stroke gasoline motors to improve the students’ learning outcomes, and (2) analysing the feasibility of the developed instructional media. This study was Research and Development. The subject of this study consisted of the 2nd-semester students of Universitas Muhammadiyah Purworejo in the academic year of 2016/2017. The data collection used a questionnaire and a test. The data were analysed using a descriptive analysis technique. The research results showed (1) the developed instructional media was feasible to be applied as instructional media, and (2) the data analysis results of the control class and the experiment class reached the mean scores of 75.80 and 83.25 respectively. It means there was a significant difference between students using the developed instructional media and those who did not.